2021
DOI: 10.3389/fendo.2021.688269
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bisphosphonates on Fracture Healing Time and Changes in Bone Mass Density: A Meta-Analysis

Abstract: BackgroundOsteoporosis is a common complication of acute fracture, which can lead to fracture delayed union or other complications and resulting in poor fracture healing. Bisphosphate is a common anti-osteoporosis drug, but its application in fracture patients is still controversial because of its inhibitory effect on bone resorption.MethodStudies were acquired from literature databases in accordance with established inclusion criteria. Standard mean difference (SMD) and 95% confidence intervals (Cls) were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 66 publications
2
18
2
2
Order By: Relevance
“…Early keyword co-occurrence analysis found that alendronate was the most frequently used in clinical use. According to the most citations of 50 articles in recent 2 years, zoledronic acid was used most frequently, which was consistent with the results of Gao et al [ 38 ]. After long-term bisphosphonate medication, patients with osteoporosis will re-evaluate the appropriate response.…”
Section: Discussionsupporting
confidence: 89%
“…Early keyword co-occurrence analysis found that alendronate was the most frequently used in clinical use. According to the most citations of 50 articles in recent 2 years, zoledronic acid was used most frequently, which was consistent with the results of Gao et al [ 38 ]. After long-term bisphosphonate medication, patients with osteoporosis will re-evaluate the appropriate response.…”
Section: Discussionsupporting
confidence: 89%
“…Pooled analysis of the timing studies also did not show any significant difference in fracture healing time between early (<1 month) and late (>1 month) bisphosphonate initiation following surgery [two studies; MD: −0.20, 95% CI: −1.03 to 0.63; p = 0.64]. Gao et al 42 also did not find any significant difference in fracture healing time between the bisphosphonate and the pooled comparator group [five studies; SMD: 0.17, 95% CI: −0.09 to 0.42; p = 0.21]. However, in their meta-analysis, studies with prior bisphosphonate use were analyzed together along with the studies where it had been initiated after surgery.…”
Section: Effect Of Timing Of Therapy On Fracture Healingmentioning
confidence: 96%
“…In another meta-analysis by Xue et al, 40 42 also did not find any significant difference in fracture healing time between the bisphosphonate and the pooled comparator group [five studies; SMD: 0.17, 95% CI: −0.09 to 0.42; p = 0.21]. However, in their meta-analysis, studies with prior bisphosphonate use were analyzed together along with the studies where it had been initiated after surgery.…”
Section: Effect Of Timing Of Therapy On Fracture Healingmentioning
confidence: 96%
See 1 more Smart Citation
“…В метаанализе 16 клинических исследований, включивших 5 022 больных остеопорозом с переломами и остеотомиями, отмечено отсутствие отрицательного влияния БФ на скорость сращения переломов, что дает основание рекомендовать их назначение в послеоперационном периоде [44].…”
Section: эффективность золедроновой кислоты после переломов у больных...unclassified